PROFITABILITY AS THE MAIN DETERMINING FACTOR OF THE FIRM VALUE - Derudebu Talunohi; Eka Bertuah (Universitas Airlangga, 2022)
This research finds out how profitability plays to the firm value, both as a factor that directly affects and also as a factor that can mediate the structure of capital, the growth of the company and the size of the company to the value of the company. The research population is a food and beverage sub-sector company registered in the IDX Period 2015-2019. Using the purposive sampling method, the research sample used 12 companies and there were 60 observed data. This study used regression analysis of panel 2 SLS data. Results show GLS (Generalized Least Square) with Random Effect Model as the best estimates model. Results showed that profitability affects the value of the company while the capital structure, company’s growth and size have no effect on the firm value. Profitability can mediate the influence of capital structure and size on the firm value, but profitability does not mediate the influence of a company's growth on the firm value.